Composition for electrolyte, electrolyte, preparation method of electrolyte and lithium ion battery

By using electrolyte compositions containing 4-iodothalonitrile and 6-fluoro-nicotinitrile in lithium-ion batteries, the problem of poor interfacial stability at high temperatures is solved, and the high-temperature cycle life and rate performance of lithium-ion batteries are significantly improved.

CN119764554AActive Publication Date: 2025-04-04STATE GRID HUNAN ELECTRIC POWER COMPANY LIMITED +3

Patent Information

Application Number
CN202411797224.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-04-04
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

In the prior art, single-particle graphite negative electrode has poor interfacial stability at high temperatures, rapid circulation capacity attenuation, and poor high-temperature rate performance, making it difficult to meet the stable operation needs of lithium-ion batteries under high temperature conditions.

Method used

An electrolyte composition is used, which contains lithium salt, film-forming additives, organic solvents and additives, among which 4-iodothalonitrile and 6-fluoro-nicotinitrile are used as additives, and a high thermal stability and low impedance interface is formed on the surface of the graphite negative electrode through their synergistic action.

Benefits of technology

It significantly improves the interface stability of single-particle graphite negative electrode at high temperatures, suppresses the increase in negative electrode polarization and gas production problems, and improves the high-temperature cycle life and high-temperature magnification performance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764554A_ABST
    Figure CN119764554A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, and discloses a composition for an electrolyte, the electrolyte, a preparation method of the electrolyte and a lithium ion battery. The composition contains a lithium salt, a film-forming additive, an organic solvent and an auxiliary agent, wherein on the basis of the total weight of the electrolyte, the content of the lithium salt is 6-20 wt%, the content of the film-forming additive is 2-6 wt%, the content of the organic solvent is 75-90 wt%, and the content of the auxiliary agent is 2-10 wt%; the auxiliary agent is a combination of 4-iodo phthalonitrile and 6-fluoro-nicotinonitrile in a mass ratio of 1: (0.5-2). When the electrolyte prepared from the composition for the electrolyte provided by the invention is applied to a lithium ion battery system of a single-particle graphite negative electrode, the interface stability of the single-particle graphite negative electrode at a high temperature can be remarkably improved, and the problems of negative electrode polarization increase and gas production are inhibited; and the high-temperature cycle life and the high-temperature rate capability of the lithium ion battery can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to an electrolyte composition, an electrolyte and a preparation method thereof, and a lithium ion battery. Background Art

[0002] In order to promote the application of renewable energy such as wind power and photovoltaic power, it has become a trend to equip electrochemical energy storage devices represented by lithium iron phosphate batteries. In order to improve the operating life of lithium iron phosphate battery energy storage systems, the use of single-grain graphite anodes with a smaller specific surface area is the current mainstream strategy. Nevertheless, in the actual operation of the energy storage system, the heat generated inside the battery is difficult to release, which easily leads to temperature rise, seriously affecting the stability of the graphite anode / electrolyte interface, and then causing problems such as battery gas bulging and capacity attenuation. It is difficult to meet the demand by simply reducing the specific surface area with single-grain graphite.

[0003] Improving the thermal stability of the graphite anode / electrolyte interface by using electrolyte high-temperature additives is an effective supplementary means, but the current mainstream high-temperature additives (such as 1,3-propane sultone and methylene disulfonate) are still not ideal. Side reactions at the anode / electrolyte interface will continue to occur during actual application, causing the battery capacity to drop. In addition, due to the large film-forming resistance of 1,3-propane sultone and methylene disulfonate, the heat generation of the battery during the cycle will be aggravated in high-rate tests, further leading to the deterioration of the battery's high-temperature performance. In order to solve the above problems, it is urgent to develop a high-temperature electrolyte that can form high thermal stability and low impedance on the surface of the graphite anode.

[0004] CN117832630A discloses an electrolyte for lithium manganese iron phosphate battery and a lithium battery, wherein the electrolyte includes a lithium salt, an organic solvent and an additive; wherein the lithium salt includes: lithium bis(fluorosulfonyl)imide salt and lithium hexafluorophosphate; the organic solvent includes: ethylene carbonate, ethyl methyl carbonate and diethyl carbonate; the additive includes: vinylene carbonate, 1,3-propane sultone, vinyl sulfate, lithium difluorophosphate and tris(trimethylsilyl)phosphate. This technical solution has a good effect on interface improvement, gas production inhibition and cycle optimization, but it still has the defects of insufficient long-term negative electrode interface stability and poor high-temperature rate performance. Summary of the invention

[0005] The purpose of the present invention is to solve the problems of poor high-temperature interface stability, rapid high-temperature cycle capacity decay and poor high-temperature rate performance of single-grain graphite negative electrodes in the prior art.

[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides a composition for an electrolyte, wherein the composition contains a lithium salt, a film-forming additive, an organic solvent and an auxiliary agent;

[0007] Wherein, based on the total weight of the electrolyte, the content of the lithium salt is 6-20wt%, the content of the film-forming additive is 2-6wt%, the content of the organic solvent is 75-90wt%, and the content of the auxiliary agent is 2-10wt%;

[0008] The auxiliary agent is a combination of 4-iodophthalonitrile and 6-fluoro-nicotinonitrile in a mass ratio of 1:0.5-2.

[0009] Preferably, based on the total weight of the electrolyte, the content of the lithium salt is 10-15wt%, the content of the film-forming additive is 3-5wt%, the content of the organic solvent is 80-83wt%, and the content of the auxiliary agent is 2-5wt%.

[0010] Preferably, the lithium salt is selected from at least two of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium bis(fluorooxalatoborate) and lithium nitrate.

[0011] Preferably, the lithium salt is a combination of lithium bis(fluorosulfonyl)imide, lithium bis(fluorooxalate)borate and lithium bis(trifluoromethylsulfonyl)imide in a mass ratio of 2-3:1:1-2.

[0012] Preferably, the film-forming additive is selected from at least three of fluoroethylene carbonate, vinylene carbonate, vinyl sulfate, 1,3-propane sultone, 1,3,6-hexanetrinitrile, methylene methanedisulfonate, tri(allyl) phosphite, tripropargyl phosphite and bis(trimethylsilyl)fluorophosphite.

[0013] Preferably, the film-forming additive is a combination of fluoroethylene carbonate, vinylene carbonate, vinyl sulfate, methylene methanedisulfonate and bis(trimethylsilyl)fluorophosphite in a mass ratio of 1:1-3:0.5-1.5:0.2-0.7:0.2-0.7.

[0014] Preferably, the organic solvent is selected from at least one of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate.

[0015] The second aspect of the present invention provides a method for preparing an electrolyte, the method comprising: contacting and mixing the components in the electrolyte composition described in the first aspect under a protective atmosphere to obtain an electrolyte.

[0016] A third aspect of the present invention provides an electrolyte prepared by the method of claim 8.

[0017] A fourth aspect of the present invention provides a lithium ion battery, the battery comprising: a positive electrode, a negative electrode, a separator and an electrolyte;

[0018] The electrolyte is the electrolyte described in the third aspect.

[0019] Through the above technical solution, the present invention has at least the following advantages:

[0020] The electrolyte prepared from the electrolyte composition provided by the present invention can be used in a lithium ion battery system with a single-grain graphite negative electrode. It can not only significantly improve the interface stability of the single-grain graphite negative electrode at high temperatures, inhibit the increase in negative electrode polarization and gas production problems, but also significantly improve the high-temperature cycle life and high-temperature rate performance of the lithium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The high temperature cycle test results of the electrolytes prepared in Example 1 and Comparative Example 1 of the present invention;

[0022] Figure 2 This is the high temperature rate test result of the electrolyte prepared in Example 1 of the present invention;

[0023] Figure 3 It is the high temperature rate charge and discharge curve of the electrolyte prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0024] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0025] As mentioned above, the first aspect of the present invention provides a composition for an electrolyte, the composition comprising a lithium salt, a film-forming additive, an organic solvent and an auxiliary agent;

[0026] Wherein, based on the total weight of the electrolyte, the content of the lithium salt is 6-20wt%, the content of the film-forming additive is 2-6wt%, the content of the organic solvent is 75-90wt%, and the content of the auxiliary agent is 2-10wt%;

[0027] The auxiliary agent is a combination of 4-iodophthalonitrile and 6-fluoro-nicotinonitrile in a mass ratio of 1:0.5-2.

[0028] The inventors of the present invention discovered during the research process that a mixture of 4-iodophthalonitrile and 6-fluoro-nicotinonitrile is specially selected as an auxiliary agent, and the two can play a synergistic role, forming a high thermal stability and low impedance negative electrode / electrolyte interface through the cyano and fluorine atoms contained therein, and at the same time, the auxiliary agent cooperates with lithium salts, film-forming additives, and organic solvents to obtain the electrolyte of the present invention, which can maintain the stable operation of the battery during high-temperature cycling, inhibit capacity decay and polarization increase, and ultimately improve the high-temperature cycle life and rate performance of the single-particle graphite negative electrode.

[0029] Preferably, based on the total weight of the electrolyte, the content of the lithium salt is 8-20wt%, the content of the film-forming additive is 2-6wt%, the content of the organic solvent is 76-83wt%, and the content of the auxiliary agent is 2-5wt%.

[0030] Preferably, based on the total weight of the electrolyte, the content of the lithium salt is 10-15wt%, the content of the film-forming additive is 3-5wt%, the content of the organic solvent is 80-83wt%, and the content of the auxiliary agent is 2-5wt%.

[0031] Preferably, the lithium salt is selected from at least two of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium bis(fluorooxalatoborate) and lithium nitrate.

[0032] Preferably, the lithium salt is a combination of lithium bis(fluorosulfonyl)imide, lithium bis(fluorooxalate)borate and lithium bis(trifluoromethylsulfonyl)imide in a mass ratio of 2-3:1:1-2. The inventors of the present invention have found that in this preferred embodiment, the high temperature rate performance of the lithium ion battery can be further improved.

[0033] Preferably, the film-forming additive is selected from at least three of fluoroethylene carbonate, vinylene carbonate, vinyl sulfate, 1,3-propane sultone, 1,3,6-hexanetrinitrile, methylene methanedisulfonate, tri(allyl) phosphite, tripropargyl phosphite and bis(trimethylsilyl)fluorophosphite.

[0034] Preferably, the film-forming additive is a combination of fluoroethylene carbonate, vinylene carbonate, vinyl sulfate, methylene disulfonate and bis(trimethylsilyl)fluorophosphite in a mass ratio of 1:1-3:0.5-1.5:0.2-0.7:0.2-0.7. In this preferred case, the high temperature cycle life of the lithium ion battery can be significantly improved.

[0035] Preferably, the organic solvent is selected from at least one of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate.

[0036] As mentioned above, the second aspect of the present invention provides a method for preparing an electrolyte, which comprises: contacting and mixing the components in the electrolyte composition described in the first aspect under a protective atmosphere to obtain an electrolyte.

[0037] Preferably, the protective atmosphere is selected from at least one of nitrogen, argon and helium.

[0038] More preferably, in the protective atmosphere, the contents of water and oxygen are each independently less than 0.1 ppm.

[0039] It should be noted that the present invention has no specific requirements on the time and temperature of the contact mixing, and the conditions known in the art can be adopted. According to a particularly preferred embodiment, the contact mixing conditions include: a temperature of 10-30°C and a time of 6-24h.

[0040] As mentioned above, the third aspect of the present invention provides an electrolyte prepared by the method of claim 8.

[0041] As mentioned above, the fourth aspect of the present invention provides a lithium ion battery, the battery comprising: a positive electrode, a negative electrode, a separator and an electrolyte;

[0042] The electrolyte is the electrolyte described in the third aspect.

[0043] Preferably, the positive electrode is a lithium iron phosphate electrode sheet, the negative electrode is a single-grain graphite electrode sheet, and the separator is a polyolefin separator.

[0044] It should be noted that the present invention has no special requirements on the content of the electrolyte in the lithium-ion battery, and any content known in the art may be used.

[0045] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, all the raw materials used are commercially available products.

[0046] Lithium bis(fluorosulfonyl)imide, purchased from J&K Technology Co., Ltd., CAS No. 171611-11-3;

[0047] Lithium borofluoride oxalate, purchased from J&K Technology Co., Ltd., CAS No. 409071-16-5;

[0048] Lithium bis(trifluoromethylsulfonyl)imide, purchased from J&K Technology Co., Ltd., CAS No. 90076-65-6;

[0049] Fluorinated ethylene carbonate, purchased from J&K Technology Co., Ltd., CAS No. 114435-02-8;

[0050] Vinylene carbonate, purchased from J&K Technology Co., Ltd., CAS No. 872-36-6;

[0051] Ethylene sulfate, purchased from J&K Technology Co., Ltd., CAS No. 1072-53-3;

[0052] Methylene methanedisulfonate, purchased from J&K Technology Co., Ltd., CAS No. 99591-74-9;

[0053] Bis(trimethylsilyl)fluorophosphite, purchased from J&K Technology Co., Ltd., CAS No. 36198-87-5;

[0054] 4-Iodophthalonitrile, purchased from J&K Technology Co., Ltd., CAS No. 69518-17-8;

[0055] 6-Fluoro-nicotinonitrile, purchased from J&K Technology Co., Ltd., CAS No. 1020253-14-8;

[0056] Fluoroacetonitrile, purchased from J&K Technology Co., Ltd., CAS No. 503-20-8;

[0057] Lithium metal flakes were purchased from Tianjin Zhongneng Lithium Industry Co., Ltd. with a purity of 99.9%;

[0058] The single-grain graphite negative electrode was purchased from Shenzhen Kejing Zhida Technology Co., Ltd. with a CAS number of 7782-42-5.

[0059] In the following examples, room temperature refers to a temperature of 23±2°C.

[0060] In the following examples, organic solvent I is a combination of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a mass ratio of 1:1:1.08;

[0061] Lithium salt I is a combination of lithium bis(fluorosulfonyl)imide, lithium bis(fluorooxalate)borate and lithium bis(trifluoromethylsulfonyl)imide in a mass ratio of 5:2:3;

[0062] Lithium salt II is a combination of lithium bis(fluorosulfonyl)imide and lithium bis(fluorooxalate) borohydride in a mass ratio of 1:5;

[0063] The film-forming additive I is a combination of fluoroethylene carbonate, vinylene carbonate, vinyl sulfate, methylene methanedisulfonate and bis(trimethylsilyl)fluorophosphite in a mass ratio of 1:2:1:0.5:0.5;

[0064] Film-forming additive II is a combination of fluoroethylene carbonate, vinylene carbonate and vinyl sulfate in a mass ratio of 1:2:2;

[0065] Auxiliary agent I is a combination of 4-iodophthalonitrile and 6-fluoro-nicotinonitrile in a mass ratio of 1:2;

[0066] Auxiliary agent II is a combination of 4-iodophthalonitrile and 6-fluoro-nicotinonitrile in a mass ratio of 2:1;

[0067] Auxiliary agent III is 4-iodophthalonitrile;

[0068] Auxiliary agent IV is 6-fluoro-nicotinonitrile;

[0069] The auxiliary agent V is a combination of 4-iodophthalonitrile and fluoroacetonitrile in a mass ratio of 1:2.

[0070] Example 1

[0071] In an argon-protected glove box (H2O and O2 contents were both less than 0.1 ppm), lithium salt, film-forming additive, organic solvent, and auxiliary agent were contacted and mixed (temperature was 25°C, time was 6 h), and stirred at room temperature for 24 h to obtain an electrolyte.

[0072] The specific types and amounts of raw materials in Example 1 are shown in Table 1. Unless otherwise specified, the other examples are carried out using the same process as Example 1, except for the raw materials and ratios used, as shown in Table 1.

[0073] Table 1

[0074]

[0075]

[0076] Example 4

[0077] This embodiment is carried out in a similar manner to that of Embodiment 1, except that an equal mass of film-forming additive II is used to replace the film-forming additive I in Embodiment 1 to obtain an electrolyte.

[0078] Example 5

[0079] This embodiment is carried out in a similar manner to that of Embodiment 1, except that an equal mass of lithium salt II is used to replace the lithium salt I in Embodiment 1 to obtain an electrolyte.

[0080] Comparative Example 1

[0081] This comparative example was carried out in a similar manner to Example 1, except that no auxiliary agent was added in this comparative example, and the amount of the organic solvent was adjusted to 8.45 g, and the type of the organic solvent remained unchanged, to obtain an electrolyte.

[0082] Comparative Example 2

[0083] This comparative example is carried out in a similar manner to Example 1, except that in this comparative example, an equal mass of auxiliary agent III is used to replace the auxiliary agent I in Example 1 to obtain an electrolyte.

[0084] Comparative Example 3

[0085] This comparative example is carried out in a similar manner to Example 1, except that in this comparative example, an equal mass of auxiliary agent IV is used to replace the auxiliary agent I in Example 1 to obtain an electrolyte.

[0086] Comparative Example 4

[0087] This comparative example is carried out in a similar manner to that of Example 1, except that in this comparative example, an equal mass of auxiliary agent V is used to replace the auxiliary agent I in Example 1 to obtain an electrolyte.

[0088] Test Case

[0089] The electrolyte prepared in the above example was subjected to performance tests, including rate performance and cycle performance.

[0090] Among them, the test method is:

[0091] With a single-grain graphite anode as the working electrode and a metal lithium sheet as the counter electrode, the electrolyte was assembled into a button-type half-cell. The specific assembly order was: positive electrode shell-single-grain graphite anode-electrolyte-diaphragm-electrolyte-metal lithium sheet-gasket-spring-negative electrode shell; after the assembly was completed, the battery was activated at 0.1C for 3 weeks, and then cycled at 45°C at 1C for 100 weeks, and its discharge specific capacity was recorded; and its discharge specific capacity was tested at 0.1C, 0.5C, 1C, 2C, and 3C respectively. The test results are shown in Table 2.

[0092] Table 2

[0093]

[0094] The present invention is exemplified in Figure 1 The high temperature cycle test results of the electrolytes prepared in Example 1 and Comparative Example 1 are provided; Figure 1 It can be seen from the results that the electrolyte prepared by the present invention can significantly improve the cycle life of the battery at a high temperature of 45°C.

[0095] The present invention is exemplified in Figure 2 The high temperature rate test results of the electrolyte prepared in Example 1 are provided in Figure 3 The high temperature rate charge-discharge curve of the electrolyte prepared in Example 1 is provided; Figure 2 , Figure 3 It can be seen from the results that the electrolyte prepared by the present invention can form a graphite negative electrode interface with high stability and low polarization, thereby significantly improving the rate performance of the battery at high temperature.

[0096] It can be seen from the above results that the electrolyte prepared by the electrolyte composition provided by the present invention, when applied to a lithium ion battery system with a single-particle graphite negative electrode, can have a higher high-temperature cycle discharge specific capacity and a higher high-temperature rate discharge specific capacity than the control example, and can significantly improve the cycle life and rate performance of the single-particle graphite negative electrode at high temperatures.

[0097] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A composition for an electrolyte, characterized in that: The composition contains lithium salt, film-forming additive, organic solvent and auxiliary agent; Wherein, based on the total weight of the electrolyte, the content of the lithium salt is 6-20wt%, the content of the film-forming additive is 2-6wt%, the content of the organic solvent is 75-90wt%, and the content of the auxiliary agent is 2-10wt%; The auxiliary agent is a combination of 4-iodophthalonitrile and 6-fluoro-nicotinonitrile in a mass ratio of 1:0.5-2.

2. The composition according to claim 1, wherein Based on the total weight of the electrolyte, the content of the lithium salt is 10-15wt%, the content of the film-forming additive is 3-5wt%, the content of the organic solvent is 80-83wt%, and the content of the auxiliary agent is 2-5wt%.

3. The composition according to claim 1 or 2, wherein The lithium salt is selected from at least two of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium bis(fluorooxalatoborate) and lithium nitrate.

4. The composition according to claim 3, wherein The lithium salt is a combination of lithium bis(fluorosulfonyl)imide, lithium bis(fluorooxalate)borate and lithium bis(trifluoromethylsulfonyl)imide in a mass ratio of 2-3:1:1-2.

5. The composition according to claim 1 or 2, wherein The film-forming additive is selected from at least three of fluoroethylene carbonate, vinylene carbonate, vinyl sulfate, 1,3-propane sultone, 1,3,6-hexanetrinitrile, methylene methanedisulfonate, tri(allyl) phosphite, tripropargyl phosphite and bis(trimethylsilyl)fluorophosphite.

6. The composition according to claim 5, wherein The film-forming additive is a combination of fluoroethylene carbonate, vinylene carbonate, vinyl sulfate, methylene methanedisulfonate and bis(trimethylsilyl)fluorophosphite in a mass ratio of 1:1-3:0.5-1.5:0.2-0.7:0.2-0.

7.

7. The composition according to claim 1 or 2, wherein The organic solvent is selected from at least one of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate.

8. A method for preparing an electrolyte, characterized in that: The method comprises: contacting and mixing the components in the electrolyte composition according to any one of claims 1 to 7 under a protective atmosphere to obtain an electrolyte.

9. The electrolyte prepared by the method according to claim 8.

10. A lithium ion battery, characterized in that: The battery comprises: a positive electrode, a negative electrode, a separator and an electrolyte; The electrolyte is the electrolyte according to claim 9.

Citation Information

Patent Citations

  • Adaptive electrolyte of lithium iron manganese phosphate battery and lithium battery

    CN117832630A

  • Additive for lithium battery electrolyte, lithium battery electrolyte and lithium battery

    CN116014243A

  • Electrolyte, preparation method and application thereof and lithium battery

    CN117199519A

  • Dye and method for producing the same

    JP2011068793A

  • Additive for non-aqueous electrolyte, non aqueous electrolyte for lithium secondary battery comprising the same, and lithium secondary battery

    KR1020170110521A

Cited By

  • Composition for electrolyte, electrolyte as well as preparation method and application of electrolyte

    CN120674589A